Compensation Method, Diakoptics, and MATE - Jean Mahseredjian; Boris Bruned; Anas Abusalah (IEEE Access)
This paper demonstrates how the Compensation method relates to the bordered-block- diagonal solution of power grids for the computation of power system transients. It is shown that it also relates to diakoptics and englobes other algorithms, such as the Multi Area Thevenin Equivalent (MATE) method. Implementation issues and potential inefficiencies are also discussed. The aim is to create a reference for avoiding confusion in the literature, for eliminating misconceptions and for supporting future research.